Age-Related Differences in the Expression of Most Relevant Mediators of SARS-CoV-2 Infection in Human Respiratory and Gastrointestinal Tract - Berni Canani, Roberto; Comegna, Marika; Paparo, Lorella; Cernera, Gustavo; Bruno, Cristina; Strisciuglio, Caterina; Zollo, Immacolata; Gravina, Antonietta Gerarda; Miele, Erasmo; Cantone, Elena; Gennarelli, Nicola; Nocerino, Rita; et al. (Frontiers in Pediatrics, 2021)
Background: Clinical features of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection seem to differ in children compared to that in adults. To explore the origin of age-dependent clinical features of coronavirus disease 2019 (COVID-19), we comparatively evaluated the expression in healthy children and adult subjects of the most relevant mediators of the SARS-CoV-2 infection: angiotensin-converting enzyme 2 (ACE2), ACE1, transmembrane serine protease-2 (TMPRSS2) and neuropilin-1 (NRP1), at upper respiratory tract and small intestine level. Methods: Expression of ACE2, ACE1, TMPRSS2 and NRP1 in nasal epithelium, collected by a cytology brush, and in small intestinal epithelial biopsies was performed by quantitative real-time PCR analysis. Results: We found no difference in ACE2, ACE1, and TMPRSS2 expression in the nasal epithelium between children and adult subjects. Whereas, nasal epithelium NRP1 expression was lower in children compared to that in adults. ACE2 expression was more abundant in the small intestine of children compared to that in adults. Opposite ACE1 expression profile was observed in the small intestine of children compared to that in adults. Intestinal TMPRSS2 and NRP1 expression was similar in the two study populations. Conclusions: The lower severity of SARS-CoV-2 infection observed in children may be due to a different expression of nasal NRP1, that promotes the virus interaction with ACE2. Whereas, the common findings of intestinal symptoms in children could be due to a higher expression of ACE2 at this level. The insights from these data will be useful in determining the treatment policies and preventive measures of COVID-19.